Botánica para arquitectos del siglo XXI - Molina Prieto, Luis Fernando (UNIVERSIDAD ANTONIO NARIÑO, 2009)
The following article proposes a reflection around the capability and competency of Colombian architecture graduates for landscaping their own projects; the way in which those architects represent trees graphically without names; the lack of knowledge —because it was never taught— regarding the species selected for urban tree planting as well as theirbotanical features; and the economic effects of unplanned tree populations in urban settings. In addition, it includes some of the foreign species reported for causing severe damageto the physical structure of Colombian cities and villages. As a conclusion, the article suggests that local architectureschools should revise their curriculum, in order to include a botanical study of urban trees and shrubs, their names and their features, so the new alumni can rely on their academic background when it comes to selecting and planting trees in our cities in the future.